2008
DOI: 10.1002/hep.22162
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cδ mediates cyclic adenosine monophosphate–stimulated translocation of sodium taurocholate cotransporting polypeptide and multidrug resistant associated protein 2 in rat hepatocytes†

Abstract: Cyclic adenosine monophosphate (cAMP) stimulates translocation of Na ؉ -taurocholate (TC) cotransporting polypeptide (Ntcp) and multidrug resistant associated protein 2 (Mrp2) to the plasma membrane. Because cAMP activates phosphoinositide-3-kinase (PI3K) and protein kinase C (PKC) activation is PI3K-dependent, the aim of the current study was to determine whether cAMP activates conventional and novel PKCs in hepatocytes and whether such activation plays a role in cAMP-stimulated Ntcp and Mrp2 translocation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 53 publications
6
48
1
Order By: Relevance
“…PMA, a known activator of conventional and novel PKCs, activates p38 MAPK in LNCaP prostrate cancer cells (40), and PKC␦ has been shown to activate p38 MAPK (16) via MKK3 (27) in cardiac myocytes. We have recently reported that cAMP activates PKC␦ in hepatocytes (37). These results raise the possibility that cAMP-induced p38 MAPK activation may be mediated via cAMP-induced activation of PKC␦.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…PMA, a known activator of conventional and novel PKCs, activates p38 MAPK in LNCaP prostrate cancer cells (40), and PKC␦ has been shown to activate p38 MAPK (16) via MKK3 (27) in cardiac myocytes. We have recently reported that cAMP activates PKC␦ in hepatocytes (37). These results raise the possibility that cAMP-induced p38 MAPK activation may be mediated via cAMP-induced activation of PKC␦.…”
Section: Discussionmentioning
confidence: 74%
“…A cell surface protein biotinylation method as previously described by us (37,45,46) was used to assess Mrp2 translocation in hepatocytes and HuH-7 cells. Briefly, following various treatments, cell surface proteins were biotinylated by exposing hepatocytes to sulfo-NHS-LC-biotin (0.5 mg/ml; Pierce) followed by preparation of cell lysate used to determine biotinylated and total Mrp2 mass using immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9D-F), which is in line with an involvement of PKC-isoforms in bile secretion. 21,26,46,47 The identification of the responsible isoform needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this PP2B-mediated pathway, NTCP's microfi lament-dependent insertion and retrieval from the plasma membrane is regulated by PI3-kinase ( 68 ). This PI3-kinase stimulated translocation is thought to be mediated in part via protein kinase C delta, as well as other signaling pathways (112)(113)(114)(115).…”
Section: Regulation Of Bsep Expression and Activitymentioning
confidence: 99%